The "HUGO BOSS" connection: Achieving global brand consistency across countries - Phau, Ian; Matthiesen, Insa (Henry Stewart Publications, 2005)
In the quest for globalisation, luxury brands are affected by brand image inconsistencies across countries. With greater regularity of consumer travel and increasing international media, consumers expect brands to deliver the same values on a worldwide basis. In other words, consumers are not disposed to tolerate inconsistencies in terms of the core concept of the brand. Hence, brand image inconsistencies harm the overall brand reputation and need to be corrected. This case study uses HUGO BOSS, one of the leading international fashion groups, as an exemplar in order to provide a simple and exploratory investigation of a brand suffering from a perception gap abroad. Australia constitutes the foreign country for this study. This case outlines the rising demand for global luxury products in Australia and the growth of HUGO BOSS as well as its future perspectives in the Australian market. This empirical investigation addresses the perception gap of the HUGO BOSS brand by examining customers' level of brand knowledge in terms of brand awareness and familiarity with the company's different brands and labels, their brand perceptions and associations as well as the brand personality that HUGO BOSS possesses in Australia. The case study proposes that HUGO BOSS has been successful in establishing a unique brand identity as an international fashion label for high-quality business wear for men, but that the company's other brand attributes are less apparent for consumers and that the depth and variety of the brand is often not fully understood by its customers.